The category of verb tense:semantic and cognitive analysis (Eurasian Journal of Philology Science and Education, 2016)
This paper deals with the problem of classification of the grammatical category of verb tense which remains undefined in the practical grammar of the Kazakh language. Several cognitive models of time are identified in the language, defined by the cultural-gnostical experience of the ethnic group and aspects functioning in the speech of the language. It is presumed that the cognitive approach in the framework of the cognitive theory of time and aspect may lead to better understanding of the grammatical meaning and function of the verb tense.
Keywords: categorization of verb tenses; cognitive grammar; con¬cept; cognitive model; frame semantics; categorization; conceptualization